Legal Protection for Consumers Against Digital Black Campaign Practices in the Skincare Industry in Indonesia - Linsepda Limbong; Evi Kongres (UNISSULA, 2025)
Black campaign practices in Indonesia’s skincare industry pose a serious threat to consumers, especially in today’s digital landscape where information spreads rapidly through social media, influencers, and anonymous accounts. These practices often involve false claims about product safety or effectiveness, manipulated reviews, and paid endorsements disguised as genuine testimonials. The impact includes misinformation, economic losses, and potential health risks. Indonesia has a relatively comprehensive legal framework, including the Consumer Protection Law (Law Number 8 of 1999), the ITE Law, the Anti-Monopoly Law, and BPOM Regulation Number 18 of 2024. However, overlapping institutional authority, difficulties in proving digital violations, and low consumer legal awareness hinder effective enforcement. Current efforts, such as BPOM’s revocation of distribution permits and consumer education by BPKN and YLKI, are positive but inadequate in addressing the complexity of black campaigns. This research uses a normative-juridical approach to analyze the legal framework, identify regulatory and enforcement gaps, and propose strategic measures. These include strengthening regulations, establishing an integrated complaint mechanism, enhancing digital forensic capabilities, and improving consumer literacy. The findings highlight the need for a comprehensive normative and conceptual strategy supported by regulations, oversight bodies, and digital awareness to create a fair and transparent skincare market in Indonesia.